Psychosocial situation of families with one and many children in the perception of children - Ochojska, Danuta; Marmola, Małgorzata; Węgrzyn-Białogłowicz, Krystyna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The aim of our research was to determine how the children from single-child and multi-child families, assess the situation in the family. It analyzed the relationships in families, depending on the number of offspring, what is the level of consistency in the relationship ties between individual family members and the level of adaptability, namely the ability to make changes in the family. A questionnaire of our own design was used at the study, Family Adaptability and Cohesion Scales and Parent-Adolescent Communication Scales D.H. Olson and associates.
Keywords: one-child family; multi-child family; cohesion; adaptability; interpersonal communication